2022
DOI: 10.1002/poi3.297
|View full text |Cite
|
Sign up to set email alerts
|

The Internet regulation turn? Policy, Internet and technology

Abstract: During a chaotic time for most in which our virtual world, made possible through the internet and its affordances, Policy & Internet sought the voices of scholars, practitioners, policymakers, and higher degree researchers to rethink our internet, its policy and the surrounding communication technology within our contemporary society. One emerging and overarching theme became apparent as our network of global scholars provided their insights into the academic puzzle and broader societal impact surrounding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…With the development and popularity of Internet technology [16,17], China's online shopping market continues to develop rapidly, and shopping websites are built in more diverse forms and styles, with richer functions [18]. Most shopping websites are equipped with rich product categories, beautiful pictures, clear site navigation, intelligent site search, and other elements [19].…”
Section: Introductionmentioning
confidence: 99%
“…With the development and popularity of Internet technology [16,17], China's online shopping market continues to develop rapidly, and shopping websites are built in more diverse forms and styles, with richer functions [18]. Most shopping websites are equipped with rich product categories, beautiful pictures, clear site navigation, intelligent site search, and other elements [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, Internet regulation requires the government to invest a large amount of research and development platform costs in the early stage of regulation. It has a high supervision cost in the early stage, but the marginal cost tends to 0 when the number of enterprises under supervision increases in the later stage (Stilinovic & Hutchinson, 2022). Based on the regulation theory and the "stimulus-behavior" theory, scholars have found that both kinds of regulation methods can promote enterprises to adopt low-carbon production behaviors (Stilinovic & Hutchinson, 2022;Wei et al, 2021).…”
Section: The Influence Of Traditional and Internet Regulation On Low-...mentioning
confidence: 99%
“…By combing the research literature on government regulation, it is found that there are significant differences between the two types of regulation in terms of regulation mode, regulation subject, regulation efficiency and regulation platform ( (Muller, 2018;Munkler, 2018;Stilinovic & Hutchinson, 2022). The differences between the two regulatory approaches are shown in Table 1.…”
Section: The Influence Of Traditional and Internet Regulation On Low-...mentioning
confidence: 99%
“…In recent years, with the continuous popularization and improvement of the network infrastructure, the internet has developed rapidly worldwide [1][2][3]. As a result, millions of smart terminals are connected to the internet, especially as far as mobile devices are concerned [4].…”
Section: Introductionmentioning
confidence: 99%